Spectroscopic insights into the Photoreduction of Cytochrome c with UVA-Vis Light Irradiation - Cao, Hong-Yu; Liu, Yan-Wei; Tang, Qian; Zhao, Ji-Min; Guo, Xiang-Jin; Zheng, Xue-Fang (Protein and Peptide Letters, 2015)
With the particular conjugation structure in the heme prosthetic group, Cyt c shows unusual functions similar to chlorophyll while irradiated by specific wavelength of UV-Vis lights. To further reveal mechanism of the photo-irradiation of Cyt c, we then studied various external factors that may influence the photo induced process. The absorbance intensity increase of band (317 nm) and Q band (520 nm and 549 nm)indicated Cyt c in phosphate-buffered saline within N2 atmosphere was photoreduced to Fe(II) Cyt c. Irradiated by 410 nm, the photoreduction process was facilitated by Met. But Trp, Tyr and Phe impeded the process due to their light absorbance abilities. In addition, the results of fluorescence and CD spectra indicated that the microenvironment polarity of Trp residue varied during the photoreduction process. And the secondary structure of Cyt c changed with lower &#945-helix/βsheet ratio. The photoreduction mechanism of Cyt c was intramolecular electron transferand porphyrin cation radicals were generated. The protein structure of Cyt c changed as well as part of the photoreduction.
Keywords: photoreduction